A Valuable Publication - Gasparyan, Seda (Armenian Folia Anglistika, 2015)
Much More than MetaphorMaster Tropes of Artistic Language and ImaginationElzbieta Chrzanowska-KluczewskaFrankfurt am Main: Peter Lang, 2013, 196 pp.